2021
DOI: 10.1210/clinem/dgab055
|View full text |Cite
|
Sign up to set email alerts
|

Robust Neutralizing Antibodies to SARS-CoV-2 Develop and Persist in Subjects with Diabetes and COVID-19 Pneumonia

Abstract: Purpose The aim of this study was to characterise the kinetics and durability of neutralizing antibody (Nab) response against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the presence of hyperglycemia. Methods Using a lentiviral-vector-based SARS-CoV-2 neutralization assay to measure Nabs, we characterised 150 patients randomly selected from a cohort of 509 patients with confirmed COVID-19 pneumonia. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 46 publications
5
37
0
1
Order By: Relevance
“… 2 A recent excellent systematic review on the immune response in Covid‐19 patients reported the earliest detectability of IgG to occur at a median of 12 days PSO or PCR‐confirmed diagnosis, to reach a peak at a median of 25 days and to start declining around 60 days. 23 Findings on IgG persistence are largely consistent across studies with positive IgG results being reported for all time points of serological testing, 12 , 15 , 17 , 20 , 21 , 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 up to 34–35 weeks PSO. 40 , 55 Whereas Hartley et al.…”
Section: Persistence Of Humoral Responsesupporting
confidence: 67%
See 2 more Smart Citations
“… 2 A recent excellent systematic review on the immune response in Covid‐19 patients reported the earliest detectability of IgG to occur at a median of 12 days PSO or PCR‐confirmed diagnosis, to reach a peak at a median of 25 days and to start declining around 60 days. 23 Findings on IgG persistence are largely consistent across studies with positive IgG results being reported for all time points of serological testing, 12 , 15 , 17 , 20 , 21 , 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 up to 34–35 weeks PSO. 40 , 55 Whereas Hartley et al.…”
Section: Persistence Of Humoral Responsesupporting
confidence: 67%
“…The majority of studies reported durability of IgM responses for up to 30–31 weeks, the longest time point studied. 15 , 20 , 31 , 32 , 37 , 38 , 44 , 45 , 56 , 59 Five studies reported initially positive findings followed by negative ones 21 , 36 , 43 , 54 , 59 detected as early as 14–15 weeks 21 , 43 and as late as 26–31 weeks 36 post infection. Another study reported mixed findings for different cohorts and antigens tested.…”
Section: Persistence Of Humoral Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Dispinseri et al showed that anti SARS-CoV-2 neutralizing antibodies' (Nabs) kinetic and durability were not affected by diabetes/hyperglycemia status. More importantly, Nabs positivity at the time of hospital admission conferred a protective effect, independent of diabetes status (HR 0.28, p = 0.046 (with diabetes), HR 0.26, p = 0.030 (without diabetes) [102].…”
Section: Vaccinating Diabetes Communitiesmentioning
confidence: 96%
“…Routine blood tests encompassed serum biochemistry [including renal and liver function, lactate dehydrogenase (LDH)], complete blood count with differential and C-reactive protein (CRP) as inflammation marker. Specific antibodies to different SARS-CoV-2 antigens, interferon alpha-4 and glutamic acid decarboxylase (GAD) were measured by a luciferase immunoprecipitation system (LIPS) assay, as previously described [20][21][22][23].…”
Section: Laboratory Variablesmentioning
confidence: 99%